2015
DOI: 10.1590/s0102-865020150110000001
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic changes with high infusion rates of lipid emulsion. Experimental study in swine

Abstract: PURPOSE:To evaluate hemodynamic changes caused by sole intravenous infusion of lipid emulsion with doses recommended for treatment of drug-related toxicity. METHODS:Large White pigs underwent general anesthesia, tracheal intubation was performed, and mechanical ventilation was instituted. Hemodynamic variables were recorded using invasive blood pressure and pulmonary artery catheterization. Baseline hemodynamic measurements were obtained after a 30-minute stabilization period. An intravenous bolus injection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…They also suggested that such hypersensitivity reactions typically increase the pulmonary arterial pressure (PAP) and decrease the systemic pressure 36 . ILE treatment for pigs has been associated with an increase in PAP without affecting oxygenation parameters 20,36,37 . Studies of critically ill patients have also shown that common doses of ILEs used for parenteral nutrition increase PAP 38 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also suggested that such hypersensitivity reactions typically increase the pulmonary arterial pressure (PAP) and decrease the systemic pressure 36 . ILE treatment for pigs has been associated with an increase in PAP without affecting oxygenation parameters 20,36,37 . Studies of critically ill patients have also shown that common doses of ILEs used for parenteral nutrition increase PAP 38 .…”
Section: Discussionmentioning
confidence: 99%
“… 36 ILE treatment for pigs has been associated with an increase in PAP without affecting oxygenation parameters. 20 , 36 , 37 Studies of critically ill patients have also shown that common doses of ILEs used for parenteral nutrition increase PAP. 38 However, the magnitude of the effect of ILE treatment on PAP at doses used for LAST (more than 50 times higher than those used for parenteral nutrition) on humans is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the overexpression of either Apo A1 or ABCA1 can result in an increase in cholesterol efflux and a decrease in fatty acid synthesis [ 60 ]. Moreover, high-rate infusions of intralipid increase systemic vascular resistance as well as reduce vascular compliance in both humans and animals [ 61 , 62 , 63 ]. These data raise the possibility that cholesterol efflux may contribute to aortic stiffness via its interaction with fatty acid metabolism.…”
Section: Potential Mechanisms Of Aortic Stiffness and Cholesterol mentioning
confidence: 99%